INDONESIAN DIPLOMACY AT THE ADMM-Plus (ASEAN DEFENSE MINISTERS MEETING) IN THE PHILIPPINE IN COUNTERACTING THE THREAT OF TERRORISM IN 2017 - Rosadi, Mirna; Saeri, M. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The purpose of this study is to understand why Indonesia has taken diplomatic action at the ASEAN DEFENSE MINISTERS MEETING-Plus session in the Philippines in 2017. Does Indonesia as a country that also has security disruptions want to cooperate with other ASEAN member countries to counteract regional threats that often happened specifically terrorism. According to the results of the ADMM meeting in the Counter Terrorism Working Group discussion, the Southeast Asian region is in the threat of terrorism such as the latest threat of terrorism in the Philippines and Indonesia and needs repression through a plan of action by the ASEAN Security Community (ASC). This research theoretically uses a realist perspective and uses the diplomatic theory of S.L. Roy. The formulation of all arguments, facts, and theoretical frameworks in this study is guided by the method of qualitative explanation. The technique in this study is through literature. Data obtained and collected from the official website of the ASEAN National Secretariat and the Ministry of Defense of the Republic of Indonesia (KEMHANRI), journal books, theses and then from the internet are related to the problem.This study found that at the 4th ADMM-plus Meeting in 2017, the Minister of Defense of the Republic of Indonesia exchanged views on terrorism and extremism, maritime security, non-professorial nuclear weapons, cyber security and Humanitarian Assistance and Disaster Relief (HADR). So on this basis, the Indonesian Minister of Defense, Ryamizad Ryacudu proposed an intelligence-based cooperation called